A positive feedback loop between tryptophan hydroxylase 1 and β-Catenin/ZBP-89 signaling promotes prostate cancer progression - Ge, Chengguo; Yan, Jiusong; Yuan, Xiaoyu; Xu, Guangyong (Frontiers in Oncology, 2022)
Abstract: Alterations in tryptophan (Trp) metabolism facilitate the continuous modulation of tumour progression, including tumour growth, distant metastasis and chemoresistance development. Although there is a high correlation between Trp metabolism and tumour progression, it is unknown whether and how Trp metabolism affects the development of prostate cancer. In this study, we reported that the overexpression of Trp hydroxylase 1 (TPH1) caused the upregulation of Trp hydroxylation and mediated the production of 5-hydroxytryptamine (5-HT), contributing to tumour growth and poor prognosis in patients with prostate cancer. Increase in 5-HT levels triggered the activation of the Axin1/β-catenin signaling pathway, thus enhancing cell proliferation and migration. Consequently, β-catenin cooperated with the Kruppel-type zinc-finger family transcription factor ZBP-89 to upregulate TPH1 expression, further promoting Trp hydroxylation and forming the TPH1/5-HT/β-catenin/ZBP-89/THP1 positive feedback signaling loop. Interruption of the signaling loop by the THP1 inhibitor 4-chloro-DL-phenylalanine (PCPA) significantly improved anticancer effects and suppressed lung metastasis in prostate cancer-bearing mice. Our findings revealed a mechanism by which TPH1 promotes prostate cancer growth by inducing Trp hydroxylation, and identified a novel THP1 target for an innovative prostate cancer therapeutic strategy.